An Analysis of Code-Switching on The Utterances of Agnes Mo on Daniel Mananta Network's Youtube Channel - Ryeo, Park Jin; Wicaksono, Andri; Rahmawati, Dwi; Yani, Novi; Sari, Lusi Purnama (IJLHE: International Journal of Language, Humanities, and Education, 2023)
This research aimed to analyze the phenomena of Code-Switching which examines the types and reasons for using code-switching used Agnes Monica on Daniel Mananta Network's YouTube channel entitled "Agnes Mo Pernah Punya Toxic Relationship?" which was published on February 11th, 2021. The researchers use Stockwell's (2002) theory that explains about three types of Code Switching, there are tag switching, intersetential switching, and intrasetential switching. In this research, the researchers employ a qualitative descriptive method, which is a research method that aims to explain and interpret reality and the researchers used Observation Method as the way to collect the data. The results and discussion found that there are six code-switching data, two Tag Switching data, two Intersetential Switching data, and two Intrasentential Switching data. And according to Hoffman (1991:116) in Saleh (2017:15), the researchers matched the data we found, that the reasons for the code-switching in Agnes Mo's utterances include the first one is talking about a particular topic, the second, being empathic about something, and the last the intention of clarifying the speech content for the interlocutor.